Co-stimulation of the fc receptor and interleukin-12 receptor on human natural killer cells leads to increased expression of cd25. (1st February 2018) - Duggan, Megan C.; Campbell, Amanda R.; McMichael, Elizabeth L.; Opheim, Kallan S.; Levine, Kala M.; Bhave, Neela; Culbertson, Michelle C.; Noel, Tiffany; Yu, Lianbo; Carson, WE
ABSTRACT: Natural killer (NK) cells serve a critical role in the immune response against microbes and developing tumors. We have demonstrated that NK cells produce stimulatory cytokines (e.g., IFN-γ) in response to potent stimulation via immobilized IgG (to engage Fc receptors) and interleukin (IL)-12. CD25 is a component of the high-affinity IL-2R, which promotes NK cell activation in response to low doses of IL-2 such as those released by activated T cells. We hypothesized that stimulation of NK cells via IgG and IL-12 would enhance CD25 expression and promote NK cell anti-tumor activity in response to low-dose IL-2. It was confirmed that this dual stimulation strategy significantly enhanced NK cell CD25 expression compared to unstimulated cells or cells treated with IgG or IL-12 alone. Dual stimulated NK cells also were more responsive to low-dose IL-2. Dual stimulated NK cells subsequently treated with low-dose IL-2 (10 pg/mL) displayed enhanced intracellular signaling as indicated by increased pSTAT5 levels. IFN-γ production and cytotoxicity against K562 cells by NK cells stimulated with low-dose IL-2 was comparable to that of cells treated with high-dose IL-2 (10 ng/mL). Importantly, cells isolated from head and neck cancer patients receiving the mAb cetuximab and IL-12 on a clinical trial displayed increased CD25 expression following combination therapy compared to baseline. Altogether, these findings suggest that FcR and IL-12R co-stimulation induces expression of the high-affinity IL-2R and promotes NK cell anti-tumor activity.